2022
DOI: 10.3390/v14092000
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of a Cohort of Patients with Post-Acute COVID-19 Syndrome in a Belgian Family Practice

Abstract: Fifty-five patients who suffered from COVID-19, who were still very ill after several months, with extreme fatigue, effort exhaustion, brain fog, anomia, memory disorder, anosmia, dysgeusia, and other multi-systemic health problems have been followed in a family practice setting between May 2021 and July 2022. Data extracted from the medical records of the 55 patients (40 women), mean age 42.4 (12 to 79 years), and a qualitative study of 6 of them using a semi-open-ended questionnaire allowed to highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 96 publications
0
18
0
Order By: Relevance
“…Olfaction was impacted in all but two studies (Bertuccelli et al, 2022 ; Jamoulle et al, 2022 ). Direct involvement included a persistent dysosmia in 11–57.6% of PACS patients (Ahmad et al, 2021 ; Davis et al, 2021 ; Parker et al, 2021 ; Silva Andrade et al, 2021 ; Girón Pérez et al, 2022 ; Michelutti et al, 2022 ; Tan et al, 2022 ) related to an anosmia (Ahmad et al, 2021 ; Fernández-de-Las-Peñas et al, 2021 ; Malik et al, 2022 ; Mendes Paranhos et al, 2022 ; Michelutti et al, 2022 ; Premraj et al, 2022 ; Tan et al, 2022 ), explicitly reported in 12.8% (Deer et al, 2021 ), 19.3–21.4% (Ahmad et al, 2021 ), 32.2% (Michelutti et al, 2022 ), 44% (Ser et al, 2022 ), or 55.9% (Vandersteen et al, 2021 ) of cases or hyposmia (Mendes Paranhos et al, 2022 ; Michelutti et al, 2022 ) explicitly reported in 14.7% (Vandersteen et al, 2021 ), 15.3% (Deer et al, 2021 ), or 33.1% (Michelutti et al, 2022 )of cases.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Olfaction was impacted in all but two studies (Bertuccelli et al, 2022 ; Jamoulle et al, 2022 ). Direct involvement included a persistent dysosmia in 11–57.6% of PACS patients (Ahmad et al, 2021 ; Davis et al, 2021 ; Parker et al, 2021 ; Silva Andrade et al, 2021 ; Girón Pérez et al, 2022 ; Michelutti et al, 2022 ; Tan et al, 2022 ) related to an anosmia (Ahmad et al, 2021 ; Fernández-de-Las-Peñas et al, 2021 ; Malik et al, 2022 ; Mendes Paranhos et al, 2022 ; Michelutti et al, 2022 ; Premraj et al, 2022 ; Tan et al, 2022 ), explicitly reported in 12.8% (Deer et al, 2021 ), 19.3–21.4% (Ahmad et al, 2021 ), 32.2% (Michelutti et al, 2022 ), 44% (Ser et al, 2022 ), or 55.9% (Vandersteen et al, 2021 ) of cases or hyposmia (Mendes Paranhos et al, 2022 ; Michelutti et al, 2022 ) explicitly reported in 14.7% (Vandersteen et al, 2021 ), 15.3% (Deer et al, 2021 ), or 33.1% (Michelutti et al, 2022 )of cases.…”
Section: Resultsmentioning
confidence: 94%
“…When it was reported (90%; n = 18) population size ranged from 34 (Vandersteen et al, 2021 ) to 178 496 (Parker et al, 2021 ) people with an average of 24 031 ± 54,301 patients in reviews papers and 638 ± 1,379 in cohort observational studies papers. Patients' ethnic groups were reported to be from all over the world apart from five (38.5%) reviews (Deer et al, 2021 ; Bertuccelli et al, 2022 ; De Luca et al, 2022a ; Jamoulle et al, 2022 ; Premraj et al, 2022 ) and five (71.4%) observational studies (Vandersteen et al, 2021 ; Girón Pérez et al, 2022 ; Mendes Paranhos et al, 2022 ; Michelutti et al, 2022 ; Ser et al, 2022 ) where patients where reported to come from only one country depending on teams origins. When it was clearly reported in 50% of studies ( n = 10), the average patient ages were 40- and 50-years-old.…”
Section: Resultsmentioning
confidence: 99%
“…Autonomic dysfunction is a major hypothesis of the symptom's persistency in long COVID [7,65,66]. A chronotropic incompetence or inadequate HR recovery were suggested to explain autonomic dysfunction throughout CPET values [17,67].…”
Section: Discussionmentioning
confidence: 99%
“…Long COVID patients were diagnosed according to WHO criteria and followed up for up to 39 months after acute COVID 2 . Complete clinical history was obtained using electronic health records and validated clinical scales (Duke Severity of Illness, Dartmouth Coop charts, see Supplementary Data) were used to quantify patient evolution 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Long COVID patients were diagnosed according to WHO criteria and followed up for up to 39 months after acute COVID 2 . Complete clinical history was obtained using electronic health records and validated clinical scales (Duke Severity of Illness, Dartmouth Coop charts, see Supplementary Data) were used to quantify patient evolution 2 . Whole blood samples were obtained from 48 Long COVID patients and 12 controls from the same general practice, matched for age, sex, time since acute COVID-19 and severity (47/48 patients and 12/12 mild-moderate, non-hospitalized), vaccination status and comorbidities (Supplementary Table 1) and analyzed by digital transcriptomic analysis (nCounter, Nanostring), as previously established for critical COVID-19 3 .…”
Section: Methodsmentioning
confidence: 99%